Children’s Online Cognitive Learning Through Integrated Technology and Hybrid Learning - Hayati, Nur; Muthmainah; Wulandari, Rina (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
Cognitive learning during the COVID-19 pandemic encountered many obstacles, but the use of various gadgets could be an effective solution in early childhood learning, especially to prepare them to enter the elementary school level. This study aims to describe the online cognitive learning process (OCL) in early childhood during the COVID-19 and new era of the pandemic through integrated technology and hybrid learning. This study uses a qualitative approach with a case study involving two ECE teachers and one principal. Data analysis using Miles and Huberman models. The findings of this study explain the importance of the teacher's role in OCL and its constraints, how parent-teacher collaboration is the key to successful cognitive improvement through online learning, and the implementation of OCL through effective learning to prevent learning loss. Further research in distance and hybrid learning, especially for early childhood, is expected to give birth to various new learning models and methods that are integrated with technology towards online teaching-learning when needed. Keywords: early childhood, cognitive online learning, integrated technology, hybrid learning References: Ansari, A., & Purtell, K. M. (2017). Activity settings in full-day kindergarten classrooms and children’s early learning. Early Childhood Research Quarterly, 38, 23–32. https://doi.org/10.1016/j.ecresq.2016.09.003 Bacher-Hicks, A., Goodman, J., & Mulhern, C. (2021). Inequality in household adaptation to schooling shocks: Covid-induced online learning engagement in real time. Journal of Public Economics, 193, 104345. https://doi.org/10.1016/j.jpubeco.2020.104345 Borup, J., Graham, C. R., West, R. E., Archambault, L., & Spring, K. J. (2020). Academic Communities of Engagement: An expansive lens for examining support structures in blended and online learning. Educational Technology Research and Development, 68(2), 807–832. https://doi.org/10.1007/s11423-020-09744-x Danovitch, J. H. (2019). Growing up with Google: How children’s understanding and use of internet‐based devices relates to cognitive development. Human Behavior and Emerging Technologies, 1(2), 81–90. https://doi.org/10.1002/hbe2.142 Davies, T. (2016). Mind change: How digital technologies are leaving their mark on our brains. New Media & Society, 18(9), 2139–2141. https://doi.org/10.1177/1461444816652614 Davis, A. N., Carlo, G., Gulseven, Z., Palermo, F., Lin, C.-H., Nagel, S. C., Vu, D. C., Vo, P. H., Ho, T. L., & McElroy, J. A. (2019). Exposure to environmental toxicants and young children’s cognitive and social development. Reviews on Environmental Health, 34(1), 35–56. https://doi.org/doi:10.1515/reveh-2018-0045 Dias, M. J. A., Almodóvar, M., Atiles, J. T., Vargas, A. C., & Zúñiga León, I. M. (2020). Rising to the Challenge: Innovative early childhood teachers adapt to the COVID-19 era. Childhood Education, 96(6), 38–45. https://doi.org/10.1080/00094056.2020.1846385 Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118, 105440. https://doi.org/10.1016/j.childyouth.2020.105440 Engzell, P., Frey, A., & Verhagen, M. D. (2021). Learning loss due to school closures during the COVID-19 pandemic. Proceedings of the National Academy of Sciences, 118(17), e2022376118. https://doi.org/10.1073/pnas.2022376118 Ford, T. G., Kwon, K.-A., & Tsotsoros, J. D. (2021). Early childhood distance learning in the U.S. during the COVID pandemic: Challenges and opportunities. Children and Youth Services Review, 131, 106297. https://doi.org/10.1016/j.childyouth.2021.106297 Graham, C. R., Borup, J., Pulham, E., & Larsen, R. (2019). K–12 Blended Teaching Readiness: Model and Instrument Development. Journal of Research on Technology in Education, 51(3), 239–258. https://doi.org/10.1080/15391523.2019.1586601 Hassan, M. N., Abdullah, A. H., Ismail, N., Suhud, S. N. A., & Hamzah, M. H. (2018). Mathematics Curriculum Framework for Early Childhood Education Based on Science, Technology, Engineering and Mathematics (STEM). International Electronic Journal of Mathematics Education, 14(1). https://doi.org/10.12973/iejme/3960 Hrastinski, S., Cleveland-Innes, M., & Stenbom, S. (2018). Tutoring online tutors: Using digital badges to encourage the development of online tutoring skills: Tutoring online tutors. British Journal of Educational Technology, 49(1), 127–136. https://doi.org/10.1111/bjet.12525 Hu, X., Chiu, M. M., Leung, W. M. V., & Yelland, N. (2021). Technology integration for young children during COVID‐19: Towards future online teaching. British Journal of Educational Technology, 52(4), 1513–1537. https://doi.org/10.1111/bjet.13106 Hu, X., & Yelland, N. (2017). An investigation of preservice early childhood teachers’ adoption of ICT in a teaching practicum context in Hong Kong. Journal of Early Childhood Teacher Education, 38(3), 259–274. https://doi.org/10.1080/10901027.2017.1335664 Hu, X., & Yelland, N. (2019). Changing Learning Ecologies in Early Childhood Teacher Education: From Technology to stem Learning. Beijing International Review of Education, 1(2–3), 488–506. https://doi.org/10.1163/25902539-00102005 Huber, B., Tarasuik, J., Antoniou, M. N., Garrett, C., Bowe, S. J., & Kaufman, J. (2016). Young children’s transfer of learning from a touchscreen device. Computers in Human Behavior, 56, 56–64. https://doi.org/10.1016/j.chb.2015.11.010 Jong, M. S. Y. (2016). Teachers’ concerns about adopting constructivist online game-based learning in formal curriculum teaching: The VISOLE experience. British Journal of Educational Technology, 47(4), 601–617. https://doi.org/10.1111/bjet.12247 Joubert, I., & Harrison, G. D. (2021). Revisiting Piaget, his contribution to South African early childhood education. Early Child Development and Care, 191(7–8), 1002–1012. https://doi.org/10.1080/03004430.2021.1896499 Kesäläinen, J., Suhonen, E., Alijoki, A., & Sajaniemi, N. (2022). Children’s play behaviour, cognitive skills and vocabulary in integrated early childhood special education groups. International Journal of Inclusive Education, 26(3), 284–300. https://doi.org/10.1080/13603116.2019.1651410 Kim, J. (2020). Learning and Teaching Online During Covid-19: Experiences of Student Teachers in an Early Childhood Education Practicum. International Journal of Early Childhood, 52(2), 145–158. https://doi.org/10.1007/s13158-020-00272-6 Kuhfeld, M., Soland, J., Tarasawa, B., Johnson, A., Ruzek, E., & Liu, J. (2020). Projecting the Potential Impact of COVID-19 School Closures on Academic Achievement. Educational Researcher, 49(8), 549–565. https://doi.org/10.3102/0013189X20965918 Lau, E. Y. H., & Lee, K. (2020). Parents’ Views on Young Children’s Distance Learning and Screen Time During COVID-19 Class Suspensio. Early Education and Development, 19. https://doi.org/10.1080/10409289.2020.1843925 Lau, E. Y. H., & Ng, M. L. (2019). Are they ready for home-school partnership? Perspectives of kindergarten principals, teachers and parents. Children and Youth Services Review, 99, 10–17. https://doi.org/10.1016/j.childyouth.2019.01.019 Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (Third edition). SAGE Publications, Inc. Mirau, E. (2017). Online Learning for Early Childhood Education Students [University of Victoria]. https://dspace.library.uvic.ca//handle/1828/8513 Neumann, D., Peterson, E. R., Underwood, L., Morton, S. M. B., & Waldie, K. E. (2021). The development of cognitive functioning indices in early childhood. Cognitive Development, 60, 101098. https://doi.org/10.1016/j.cogdev.2021.101098 Orben, A., & Przybylski, A. K. (2019). The association between adolescent well-being and digital technology use. Nature Human Behaviour, 3(2), 173–182. https://doi.org/10.1038/s41562-018-0506-1 Peng, P., & Kievit, R. A. (2020). The Development of Academic Achievement and Cognitive Abilities: A Bidirectional Perspective. Child Development Perspectives, 14(1), 15–20. https://doi.org/10.1111/cdep.12352 Pérez-Pereira, M., Fernández, M. P., Gómez-Taibo, M. L., Martínez-López, Z., & Arce, C. (2020). A Follow-Up Study of Cognitive Development in Low Risk Preterm Children. International Journal of Environmental Research and Public Health, 17(7). https://doi.org/10.3390/ijerph17072380 Ranjitkar, S., Hysing, M., Kvestad, I., Shrestha, M., Ulak, M., Shilpakar, J. S., Sintakala, R., Chandyo, R. K., Shrestha, L., & Strand, T. A. (2019). Determinants of Cognitive Development in the Early Life of Children in Bhaktapur, Nepal. Frontiers in Psychology, 10. https://www.frontiersin.org/articles/10.3389/fpsyg.2019.02739 Reuben, A., Arseneault, L., Belsky, D. W., Caspi, A., Fisher, H. L., Houts, R. M., Moffitt, T. E., & Odgers, C. (2019). Residential neighborhood greenery and children’s cognitive development. Social Science & Medicine, 230, 271–279. https://doi.org/10.1016/j.socscimed.2019.04.029 Richardson, J. C., Maeda, Y., Lv, J., & Caskurlu, S. (2017). Social presence in relation to students’ satisfaction and learning in the online environment: A meta-analysis. Computers in Human Behavior, 71, 402–417. https://doi.org/10.1016/j.chb.2017.02.001 Saeed, M., Malik, R. N., & Kamal, A. (2020). Fluorosis and cognitive development among children (6–14 years of age) in the endemic areas of the world: A review and critical analysis. Environmental Science and Pollution Research, 27(3), 2566–2579. https://doi.org/10.1007/s11356-019-06938-6 Schoon, I., Nasim, B., & Cook, R. (2021). Social inequalities in early childhood competences, and the relative role of social and emotional versus cognitive skills in predicting adult outcomes. British Educational Research Journal, 47(5), 1259–1280. https://doi.org/10.1002/berj.3724 Simon, L., Nusinovici, S., Flamant, C., Cariou, B., Rouger, V., Gascoin, G., Darmaun, D., Rozé, J.-C., & Hanf, M. (2017). Post-term growth and cognitive development at 5 years of age in preterm children: Evidence from a prospective population-based cohort. PLOS ONE, 12(3), e0174645. https://doi.org/10.1371/journal.pone.0174645 Singh, J., Steele, K., & Singh, L. (2021). Combining the Best of Online and Face-to-Face Learning: Hybrid and Blended Learning Approach for COVID-19, Post Vaccine, & Post-Pandemic World. Journal of Educational Technology Systems, 50(2), 140–171. https://doi.org/10.1177/00472395211047865 Szente, J. (2020). Live Virtual Sessions with Toddlers and Preschoolers Amid COVID-19: Implications for Early Childhood Teacher Education. Journal of Technology and Teacher Education, 28(2), 373–380. Taylor, M. E., & Boyer, W. (2020). Play-Based Learning: Evidence-Based Research to Improve Children’s Learning Experiences in the Kindergarten Classroom. Early Childhood Education Journal, 48(2), 127–133. https://doi.org/10.1007/s10643-019-00989-7 Thai, K. P., & Ponciano, L. (2016). Improving Outcomes for At-Risk Prekindergarten and Kindergarten Students with a Digital Learning Resource. 31. Trikoilis, D., & Papanastasiou, E. C. (2020). The Potential of Research for Professional Development in Isolated Settings During the Covid-19 Crisis and Beyond. Journal of Technology and Teacher Education, 28(2), 295–300. Troseth, G. L., & Strouse, G. A. (2017). Designing and using digital books for learning: The informative case of young children and video. International Journal of Child-Computer Interaction, 12, 3–7. https://doi.org/10.1016/j.ijcci.2016.12.002 Watanabe, N. (2019). Effective Simple Mathematics Play at Home in Early Childhood: Promoting both Non-cognitive and Cognitive Skills in Early Childhood. International Electronic Journal of Mathematics Education, 14(2). https://doi.org/10.29333/iejme/5739 Zauche, L. H., Thul, T. A., Mahoney, A. E. D., & Stapel-Wax, J. L. (2016). Influence of language nutrition on children’s language and cognitive development: An integrated review. Early Childhood Research Quarterly, 36, 318–333. https://doi.org/10.1016/j.ecresq.2016.01.015